Probing gut‐brain links in Alzheimer's disease with rifaximin - Paul V. Suhocki; James S. Ronald; Anna Mae E. Diehl; David M. Murdoch; P. Murali Doraiswamy (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2022)
Abstract Gut‐microbiome‐inflammation interactions have been linked to neurodegeneration in Alzheimer's disease (AD) and other disorders. We hypothesized that treatment with rifaximin, a minimally absorbed gut‐specific antibiotic, may modify the neurodegenerative process by changing gut flora and reducing neurotoxic microbial drivers of inflammation. In a pilot, open‐label trial, we treated 10 subjects with mild to moderate probable AD dementia (Mini‐Mental Status Examination (MMSE) = 17 ± 3) with rifaximin for 3 months. Treatment was associated with a significant reduction in serum neurofilament‐light levels (P < .004) and a significant increase in fecal phylum Firmicutes microbiota. Serum phosphorylated tau (pTau)181 and glial fibrillary acidic protein (GFAP) levels were reduced (effect sizes of −0.41 and −0.48, respectively) but did not reach statistical significance. In addition, there was a nonsignificant downward trend in serum cytokine interleukin (IL)‐6 and IL‐13 levels. Cognition was unchanged. Increases in stool Erysipelatoclostridium were correlated significantly with reductions in serum pTau181 and serum GFAP. Insights from this pilot trial are being used to design a larger placebo‐controlled clinical trial to determine if specific microbial flora/products underlie neurodegeneration, and whether rifaximin is clinically efficacious as a therapeutic.